Differential Lipidomic Characteristics of Children Born to Women with Polycystic Ovary Syndrome - Zhang, Zhirong; Liu, Yue; Lv, Jiali; Zhang, Di; Hu, Kuona; Li, Jingyu; Ma, Jinlong; Cui, Linlin; Zhao, Han (Frontiers in Endocrinology, 2021)
Objective: To describe the lipidomic characteristics of offspring born to polycystic ovary syndrome (PCOS) women (PCOS-off) and assess the associations between differential lipids and clinical phenotypes. Methods: Ultra performance liquid chromatography and mass spectrometry were performed on plasma samples from 70 PCOS-off and 71 healthy controls. The associations of differential metabolites with clinical phenotypes were examined by multiple linear regression. Results: Forty-four metabolites were significantly altered in PCOS-off, including 8 increased and 36 decreased. After stratification according to sex, 44 metabolites (13 increased and 31 decreased) were expressed differently in girls born to PCOS women (PCOS-g), most of which were glycerolipids. Furthermore, 46 metabolites (9 increased and 35 decreased) were expressed differently in boys born to PCOS women (PCOS-b), most of which were glycerophospholipids. Significant associations of metabolites with weight Z-score and HDL were found in PCOS-off. Triglycerides, low density lipoprotein cholesterol, and thyroid-stimulating hormone were separately correlated with some lipids in PCOS-g and PCOS-b. Conclusions: PCOS-off showed specific lipid profile alterations. The abnormal level of GP and SM indicated the risk of glucose metabolism and cardiovascular diseases in PCOS-off. Some lipids, such as phosphatidylcholines, lysophosphatidylcholine and sphingomyelin, may be the potential markers. The results broadened our understanding of PCOS-offs’ cardiometabolic status and emphasized more specific and detailed monitoring and management in this population.